2001
DOI: 10.1046/j.1468-3083.2001.00231.x
|View full text |Cite
|
Sign up to set email alerts
|

Skin involvement in chronic myelomonocytic leukaemia as a predictor of transformation into acute myeloid leukaemia

Abstract: We report on the case of a patient with myelodysplastic syndrome (MDS) who presented with leukaemia cutis preceding development of acute myeloid leukaemia. Leukaemic infiltration of the skin should be considered an early manifestation of leukaemic transformation and an indicator of poor prognosis in MDS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0
7

Year Published

2004
2004
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 17 publications
0
11
0
7
Order By: Relevance
“…Specific lesions are uncommon and are characterized by the presence of neoplastic cells in the skin. They are referred to as leukaemia cutis, are indicative of blastic transformation of MDS and carry a grim prognosis 8,9 . In contrast, non‐specific lesions are common, lack skin infiltration by neoplastic cells and generally they do not affect prognosis 10 .…”
Section: Introductionmentioning
confidence: 99%
“…Specific lesions are uncommon and are characterized by the presence of neoplastic cells in the skin. They are referred to as leukaemia cutis, are indicative of blastic transformation of MDS and carry a grim prognosis 8,9 . In contrast, non‐specific lesions are common, lack skin infiltration by neoplastic cells and generally they do not affect prognosis 10 .…”
Section: Introductionmentioning
confidence: 99%
“…The specific cutaneous lesions of CMML are seen very rarely with a prevalence of 10%. In some cases, CMML can be transformed to acute myeloid leukemia that is also accompanied by the lesions of myeloid leukemia cutis 9 . Vitte et al 10 reported four different clinicopathological subtypes of cutaneous involvement in CMML with different prognostic courses; myelomonocytic cell tumor, MPDCT, blastic PDCT (BPDCT) and blastic indeterminate dendritic cell tumor (BIDCT).…”
Section: Discussionmentioning
confidence: 99%
“…The differential diagnosis of a leukemic skin lesion located on the trunk includes a vast majority of cutaneous diseases, such as cutaneous malignancies, metastasis of visceral malignancies, Kaposi sarcoma, drug eruption, viral exanthem, syphilitic exanthem, pityriasis rosea, urticarial vasculitis, Sweet's syndrome, cutaneous pseudolymphoma, and cutaneous lymphomas 2 . Chronic myelomonocytic leukemia (CMML) is characterized by an absolute monocytosis greater than 1x10 9 /L in the peripheral blood that persists for at least three months. greater than 1x10 9 /L in the peripheral blood that persists for at least three months.…”
Section: Introductionmentioning
confidence: 99%
“…So far, leukaemia cutis as a herald sign of a transformation of RAEB has been reported only sporadically 5,6 . However, it is known from cases with chronic myelomonocytic leukaemia, another subtype of MDS, that leukaemic transformation in MDS patients is not infrequently accompanied by skin infiltrations 7,8 …”
Section: Reportmentioning
confidence: 99%